High Trichophyton violaceum-Induced Tinea Capitis with Isolation of Many Non-Dermatophyte Molds in Scalp Scrapings in Patients Referred to a Dermatology Clinic in Addis Ababa, Ethiopia - Bitew A; Yilma B; Taye T (Dove Medical Press, 2022)
Adane Bitew,1 Betelhem Yilma,2 Tomas Taye3 1Department of Medical Laboratory Science, College Health Sciences, Addis Ababa University, Addis Ababa, Ethiopia; 2Saint Peter's Specialized Tuberculosis Referral Hospital, Addis Ababa, Ethiopia; 3Rank Specialized Dermatology Clinic, Addis Ababa, EthiopiaCorrespondence: Adane Bitew, Department of Medical Laboratory Science, College Health Sciences, Addis Ababa University, P.O. Box: 1176, Addis Ababa, Ethiopia, Tel +251911039162, Email adane.bitew@aau.edu.etObjective: This work aimed to determine the magnitude of tinea capitis, the diversity and species composition of fungi, and the predominant dermatophytes implicated in causing tinea capitis.Methods: A prospective, cross-sectional study was conducted at a dermatology clinic. Scalp scrapings were collected and cultured, and dermatophyte and non-dermatophyte molds were identified.Results: Of 364 scalp scrapings, fungi were recovered from 301 (82.7%) clinical samples. About 60.7% of the samples were collected from women, while 39.3% were collected from male study subjects. The association between the magnitude of scalp ringworm and gender was not statistically significant (P = 0.105). Two hundred eighty study subjects were less than 15 years of age, of which 254 were culture positive. The association of tinea capitis and the age of patients was statistically significant (P = 0). Three hundred forty-nine fungal isolates were isolated, of which 54.2% were dermatophytes, while 45.8% were non-dermatophyte molds. The occurrence of dermatophytes in their decreasing order was T. violaceum (138; 73%), Trichophyton mentagrophytes (18; 9.5%), Trichophyton tonsurans (16; 8.5%), Trichophyton verrucosum (8; 4.5%), Microsporum audouinii (7; 3.7%), Trichophyton schoenleinii (1; 0.5%), and Trichophyton soudanense (1; 0.5%).Conclusion: A high prevalence rate of T. violaceum-induced tinea capitis was reported. The magnitude of scalp ringworm in adults was remarkably high. Therefore, conducting a nationwide epidemiological survey on tinea capitis regardless of age is suggested. The isolation of many non-dermatophyte molds in the current study may shade questions about the perception that tinea capitis is caused by dermatophytes only. Therefore, studies on their potential pathogenic role on skin and skin-related (nail and the scalp) infections appear to be an active field of research.Keywords: scalp ringworm, superficial mycosis, dermatophytosis, Trichophyton violaceum, Ethiopia